Employees' Independent Thinking as an Innovation: Its Impact Towards Organizational Performance in Small and Medium Enterprise - Yubiao Wei; Rovena I. Dellova (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
In the current context of fierce market competition faced by small and medium-sized enterprises (SMEs), employees' independent thinking is crucial for promoting adaptability and innovation. However, traditional managers often prioritize employees' compliance and execution over independent thinking, especially in the development of information technology. This study aims to explore the impact mechanism of employees' independent thinking ability on enterprise organizational performance, focusing on the mediating role of organizational innovation and organizational behavior and the moderating effect of employee empowerment. This empirical study employed a quantitative research design using structural equation modeling (SEM) and collected data from 427 employees randomly selected from small and medium-sized enterprises in Guangdong, China. Based on the findings, most respondents were middle-aged males with 7–9 years of work experience, employed in private firms, with an equal proportion of employees in organizations ranging from 51–250 and more than 251. The regression shows that employee independent thinking (EIT) has a strong and significant positive effect on organizational innovation and organizational behavior. It also directly improves employee performance. Organizational innovation partially mediates the relationship between EIT and performance. However, employee empowerment does not significantly influence or change the effect of independent thinking on their performance. This study highlights theoretical concepts on the relationship between independent thinking ability and enterprise organizational performance, thereby providing synergy with active employee participation for creative performance aligned with its operations and corporate management practices.